Muslim localizing democracy:a non-pesantren village in Madura as a preliminary study - Saputro, Muhammad Endy (Indonesian Journal of Islam and Muslim Societies, 2011)
The political dynamic of village in Indonesian New Order has two faces. On onehand, it is conditioned by the feudalism of villageâs leader which is monopolizedfrom one generation to other generations. On the other hand, religion can be analternative to challenge this feudalism. I explore this condition through an examinationof the role of kalebun (the villageâs leader) and kiai in a non-pesantrenvillage in Madura, Indonesia. In Madura society, kiai and its pesantren take importantrole in the process of Islamic institutionalization. Yet, in this case, theabsence of pesantren enforces the kiai to be counter-balance of the feudalism ofthe kalebun. And, the kiai claims that this counter-balance is on behalf of democracy.This article concludes with a discussion of the requirement of democracy in âIslamicâ local politics as well as in search of good local governance in postIndonesian New Order.Dinamika politik desa pada masa Orde Baru menghadapi dua realitas antagonis.Di satu sisi, pemerintahan desa dimonopoli oleh generasi tertentu yang melahirkanrezim feodal. Seorang Muslim, di lain sisi, berpotensi menjadi elan vital perlawananterhadap feodalisme tersebut. Tulisan ini berupaya menggali dua kenyataantersebut melalui analisis kepemimpinan kalebun (kepala desa) dan kiai di sebuahdesa non-pesantren di Madura, Indonesia. Pada jamaknya, dalam masyarakatMadura, kiai dan pesantren memiliki peranan penting dalam prosesinstitusionalisasi Islam. Namun, dalam studi ini, ketiadaan pesantren, membuatkiai (dengan langgarnya) berusaha membendung arus feudalisme kalebun. Sebuahtemuan menarik bahwa perlawanan sang kiai tidak atas nama Islam, tetapi demitegaknya demokratisasi di desa.